Influence of Mediterranean university campuses on taxonomic, phylogenetic, and functional diversity of urban spiders (Araneae) - Arjona, José Manuel; Reyes-Fernández, Anabel; Morano, Eduardo; Naves-Alegre, Lara; Ibáñez-Álamo, Juan Diego; Sanllorente, Olivia (Frontiers in Ecology and Evolution, 2025)
University campuses are well differentiated places from other urban areas because they are usually built to foster an educational environment, support scientific research and nature conservation. However, few studies have tested their potential benefit for urban biodiversity, which could be especially relevant in understudied hot spots, like the Mediterranean region. Spiders, as top urban predators, play a vital role in ecosystem functioning and serve as bioindicators for certain habitat alterations. Here, we investigated whether university campuses in a Mediterranean city hold higher levels of spider diversity than other non-campus urban areas. To do so, we analyzed abundance and the taxonomic, functional and phylogenetic diversity of ground-dwelling and web-weaving spider communities of three university campuses and three other non-campus urban areas in the city of Granada (Spain). Contrary to our expectations, the results suggest that university campuses harbor similar levels of spider diversity to other urban areas. Furthermore, we identified certain urban features that can significantly influence spider assemblages in cities. The presence of native and reduced maintenance along with specific surface types (i.e., herbaceous, campus buildings, pavement and bare soil) were found to enhance the diversity of the urban ground-dwelling spider communities, while web-weaving species are more susceptible to the distance to the outskirts, university campuses management or landscape coverages (i.e., herbaceous or bare soil). These findings suggest that such features should be considered when designing urban areas to promote urban biodiversity.